Planning for Rehabilitation and Closure of the Coburn Mineral Sand Mine at Shark Bay, Western Australia - Finucane, S.; Hardman, B.; Harley, D. (Mine Closure 2006: Proceedings of the First International Seminar on Mine Closure, 2006)
Gunson Resources Limited (Gunson) is developing the Coburn Mineral Sand Project (the Project) in the Gascoyne region of Western Australia (Figure 1). The Project comprises the excavation and processing of a major low-grade mineral sand deposit immediately east of the Shark Bay World Heritage Property. Approximately 2.8 Mt of Heavy Mineral Concentrate will be dry-mined from nine pits and processed on site before transport to markets. As part of the Environmental Impact Assessment (EIA) of the proposed Project, a Rehabilitation Benchmarking Study (RBS) was conducted to demonstrate whether rehabilitation was possible by providing examples of rehabilitation outcomes under similar conditions. This paper outlines the approach taken in relation to this study and discusses the key outcomes.